Analisis Faktor Demografi yang Berhubungan dengan Distres Pasien Rawat Inap Diabetes Tipe II di Yogyakarta - Raisa Farida Kafil (Journal of Health (JoH), 2019)
The high expectations and tightness of the diabetes therapy regimen is one of the biggest causes of distress in DM patients who are characterized by feelings of despair, worry about financing treatment, frustration due to uncontrolled blood glucose and blood pressure, and fear of the threat of further complications from DM. The aim of this study was to identify the demographic characteristics associated with distress in type 2 diabetes patients in Yogyakarta. There are five demographic factors identified as independent variables in this study including age, gender, education level, duration of diabetes and comorbidities. The results showed that most diabetic patients experienced mild distress (68.8%), moderate (31.3%), and severe (0%). The most associated factor with diabetes distress is the level of education [p = 0.039; 95% confidence interval (CI): 0.464-9.889] Patients with lower levels of education have a risk of 2,143 times having diabetes distress [Exp (B): 2,143)].